(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. This study aimed to investigate effects of fasting during the Ramadan month among chronic kidney disease (CKD) and hemodialysis patients. Materials and Methods. A prospective study was carried out on patients seen between August and November 2010 at two hospitals of King Saud University. Volunteers from among patients with CKD and hemodialysis patients were evaluated for kidney function and complications before, during, and after 14-hour daily Ramadan fasting for 30 days. A modified schedule for medication and dialysis regimen was provided to the participants. Results. Thirty-nine CKD patients (41.0% in stage 3 and 43.6% in stage 4) were included. There were no differences in the laboratory and clinical variables before, during, and after the fasting month. Thirty-two hemodialysis patients with a mean duration of dialysis of 4.4 ± 3.7 years were also included in the study. There was a significant increase in erythrocyte count, serum creatinine, blood urea, serum phosphorus, serum albumin, and serum uric acid levels during the fasting period. Hyperkalemia developed in 25.0% and 15.6% of the hemodialsysis patients during and after the fasting period and hyponatremia in 15.6% and 28.0%, respectively. Forty-six percent of the patients developed hypertension and 36.7% fluid overload. No adverse events requiring hospital admission were observed. Conclusions. Fourteen-hour fasting for one month was tolerated by CKD and hemodialysis patients, although there were considerable changes among hemodialysis patients in some of the blood chemistry variables. No serious adverse events occurred.